2019
DOI: 10.1007/s40279-019-01217-3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Energy Availability in Reproductive Function in the Female Athlete Triad and Extension of its Effects to Men: An Initial Working Model of a Similar Syndrome in Male Athletes

Abstract: The Female Athlete Triad represents three interrelated conditions of (i) low energy availability (energy deficiency), presenting with or without disordered eating, (ii) menstrual dysfunction, and (iii) poor bone health, each of which can exist along a continuum of severity ranging from mild and moderate subclinical health concerns to severe clinical outcomes, including eating disorders, amenorrhea, and osteoporosis. This review provides a brief overview of the Female Athlete Triad, including updating the curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 86 publications
1
67
0
5
Order By: Relevance
“…While the state of low energy availability (LEA) produces a myriad of physiological consequences in women and supposedly men, it is associated specifically with the development of low testosterone in men (110). The mechanism for such a change appears consistent with earlier work supporting the development of hypogonadotropic hypogonadism as with extensive caloric deficient, weight loss and restricted food intake (see prior discussions).…”
Section: Male Triad/red-ssupporting
confidence: 55%
See 1 more Smart Citation
“…While the state of low energy availability (LEA) produces a myriad of physiological consequences in women and supposedly men, it is associated specifically with the development of low testosterone in men (110). The mechanism for such a change appears consistent with earlier work supporting the development of hypogonadotropic hypogonadism as with extensive caloric deficient, weight loss and restricted food intake (see prior discussions).…”
Section: Male Triad/red-ssupporting
confidence: 55%
“…Recently, DeSouza and associates have proposed an expansion of the scope of the Triad condition and use of the term to encompass not only the historic population of women but also males (110). Interestingly, earlier researchers had drawn an analogy between the development of menstrual disruptions in exercising women and the observation of low testosterone in men but had never applied the Triad terminology to men (111,112).…”
Section: Male Triad/red-smentioning
confidence: 99%
“…Insufficient dietary energy intake can disrupt normal homeostasis in humans, an effect that can be exacerbated by the energetic demands of sports and exercise. The models of the female athlete triad (De Souza et al 2014), its male counterpart (De Souza et al 2019a, 2019bTenforde et al 2016) and the relative energy deficiency in sport (RED-S) (Mountjoy et al 2018a) provide theoretical frameworks for physiological dysregulations and negative health and performance outcomes triggered by a low energy intake relative to energy expenditure in humans who exercise regularly. Lying at their core is the concept of energy availability (EA), a concept that provides a single numerical value that is thought as the aetiological factor of a broad range of hormonal, metabolic and physiological dysregulations triggered by energy deficiency (De Souza et al 2014, 2019bMountjoy et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, in a recent review suggesting that running mileage alone is not enough to predict the low T concentrations [52], it was proposed that the alterations in the endocrine-reproductive hormonal system observed in endurance runners are related to the development of low energy availability (LEA) [33]. In healthy and active women, it has been established that an adequate energy intake is ≥45 kcal/kg FFM [53]; whether intake in men is similar is currently under debate [52]. In our study, runners reported an energy intake lower than 45 kcal/kg FFM initially and especially at 3 months, a period when the runners ran more km/week, and basal T and LH concentrations were the lowest of the season.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, runners reported an energy intake lower than 45 kcal/kg FFM initially and especially at 3 months, a period when the runners ran more km/week, and basal T and LH concentrations were the lowest of the season. De Souza [53] concluded that it is difficult to consume the energy required by athletes who perform chronic strenuous exercise, resulting in an energy deficit that causes alterations in the hypothalamic-pituitary-gonadal axis.…”
Section: Discussionmentioning
confidence: 99%